2018
DOI: 10.1007/s11356-018-3048-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of metals from group 10 (Ni, Pd, and Pt) and 11 (Cu, Ag, and Au) with human blood δ-ALA-D: in vitro and in silico studies

Abstract: Mammalian δ-aminolevulinate dehydratase (δ-ALA-D) is a metalloenzyme, which requires Zn(II) and reduced thiol groups for catalytic activity, and is an important molecular target for the widespread environmental toxic metals. The δ-ALA-D inhibition mechanism by metals of Group 10 (Ni, Pd, and Pt) and 11 (Cu, Ag, and Au) of the periodic table has not yet been determined. The objective of this study was to characterize the molecular mechanism of δ-ALA-D inhibition caused by the elements of groups 10 and 11 using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Focusing on diphenyl diselenide and its derivatives, the more precise findings include mainly those toward the enzyme δ-aminolevulinate dehydratase (δ-ALA-D). δ-ALA-D catalyzes the condensation of two molecules of 5-aminolevulinic acid to porphobilinogen, a monopyrrol precursor of prosthetic group heme, and due to its sulfhydryl nature, it has been commonly used in toxicological researches as an indicator of toxicity caused by pro-oxidant agents (Chaudiere et al 1992 ; Ecker et al 2018 ; Klimaczewski et al 2018 ; Rocha et al 2012c ).…”
Section: Toxicity Of Organoselenium Compoundsmentioning
confidence: 99%
“…Focusing on diphenyl diselenide and its derivatives, the more precise findings include mainly those toward the enzyme δ-aminolevulinate dehydratase (δ-ALA-D). δ-ALA-D catalyzes the condensation of two molecules of 5-aminolevulinic acid to porphobilinogen, a monopyrrol precursor of prosthetic group heme, and due to its sulfhydryl nature, it has been commonly used in toxicological researches as an indicator of toxicity caused by pro-oxidant agents (Chaudiere et al 1992 ; Ecker et al 2018 ; Klimaczewski et al 2018 ; Rocha et al 2012c ).…”
Section: Toxicity Of Organoselenium Compoundsmentioning
confidence: 99%
“…The previous in vitro assays have indicated that the mechanism of Hsδ-AlaD (or mammalian δ-AlaD) and Dmδ-AlaD inhibition by organoselenium compounds involves Cys oxidation because dithiothreitol (DTT red ) could reactivate the enzyme from these sources [10,11,24,29,30,98]. The Se … S interaction could lead to the formation of the selenenyl sulfide bond (Se-S) [99,100], an adduct between the protein and the selenium compound, by means of a nucleophilic attack of the thiolate moiety of Cys124 (122) to the Se atom of either DPDS or PSA.…”
Section: Organoselenium Molecular Docking Studymentioning
confidence: 99%